МЕТАФОРИЧЕСКОЕ ВЫРАЖЕНИЕ КОНЦЕПТА «РОДИНА» В РУССКОМ ЯЗЫКОВОМ СОЗНАНИИ - Турабаева, Н.А. (SCIENCE and SOCIETY, 2025)
This article examines the metaphorical expression of the concept of Motherland in the Russian linguistic consciousness. Metaphors today have gone beyond the usual trope; they are considered by researchers as forms of expression of consciousness. The article analyzes the metaphorical embodiments of the Motherland as the Motherland, the Motherland as a shrine, the Motherland as a family and home, and the role of personification in enhancing emotionality.